(untitled) (Journal of Dhaka Medical College, 2021)
Prematurity and low birth weight contributes to 27.8% of neonatal deaths in rural areas of Bangladesh. Fluid, electrolyte and metabolic abnormalities are the commonest derangements encountered in preterm infants due to their renal immaturity and relatively immature skin. Premature infant are at increased risk of developing dehydration or overhydration4. Therefore, high index of suspicion, prompt recognition and thorough understanding of common electrolyte abnormalities are necessary to improve neonatal outcome. Appropriate fluid and electrolyte management is essential for better neonatal outcome. Objectives: To identify the serum electrolytes abnormalities in preterm low birth weight neonates. Methodology: It was a cross- sectional study and carried out in the Department of Neonatology, Dhaka Medical College Hospital, Dhaka between January 2017 to August 2017. Information was collected who gave consent and participated in the study willingly. The sample size was 50. Patients admitted in the above mentioned hospital and after meeting the inclusion and exclusion criteria a simple random sampling technique was applied for selecting the study subjects. Results: Fifty preterm LBW neonates fulfilling the inclusion criteria were studied during this study period. Abnormal electrolytes were documented in 20(40%) out of 50 preterm LBW neonates and electrolyte status was normal in 30(60.0%) cases. Of 20 neonates who had abnormal electrolytes, hyperkalemia was the predominant electrolyte abnormality found in 8(16.0%) neonates, hyponatremia was found in 7(14.0%), hypokalemia in 3(6.0%) and hypernatremia 2(4.0%). Conclusion: Electrolyte abnormalities are common in preterm LBW neonates. So, identification of electrolyte abnormalities and proper management of fluid and electrolytes and close monitoring are important. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 145-148